2010
DOI: 10.28945/1175
|View full text |Cite
|
Sign up to set email alerts
|

Encouraging SME eCollaboration – The Role of the Champion Facilitator

Abstract: Technology has done many things for small businesses. In one sense small business has been harmed through the advance of technology, which, from a competitive perspective, has made the world a much smaller place. To balance this, technology now provides the means for small businesses to collaborate and build complementary skills to provide a better competitive standing in the world market. Electronically enhanced collaboration, or eCollaboration, allows firms to transcend the boundaries of space and time, perm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Some researchers have suggested that many firms collaborate to learn new skills or acquire tacit knowledge (Nooteboom 2004;Jones and Burgess 2010;Lin et al 2011). Today knowledge sharing is important to be "innovative" and "value adding" in organisational innovation (Freeman and Soete 1990; Cricelli and Grimaldi 2009).…”
Section: Internal Incentives: Learn New Skills and Knowledge Transfermentioning
confidence: 99%
“…Some researchers have suggested that many firms collaborate to learn new skills or acquire tacit knowledge (Nooteboom 2004;Jones and Burgess 2010;Lin et al 2011). Today knowledge sharing is important to be "innovative" and "value adding" in organisational innovation (Freeman and Soete 1990; Cricelli and Grimaldi 2009).…”
Section: Internal Incentives: Learn New Skills and Knowledge Transfermentioning
confidence: 99%
“…Knowledge work today is increasingly collaborative, because practical problems to be addressed are often complex and span across specializations. Such collaboration is difficult because of the traditionally individualistic culture of the professions (Jones & Burgess, 2010).…”
Section: Relating Activity Theory and Collaborationmentioning
confidence: 99%